(untitled) (BIRDEM Medical Journal, 2012)
Chorioangioma constitutes the commonest benign growth of placenta. It consists of a benign angioma arising from chorionic tissue. Chorioangioma of the placenta most often goes unnoticed. With the advent of gray scale and color flow ultrasonography in prenatal diagnosis these tumours can be easily detected antenatally. It has potentially serious fetal risks and so the pregnancy needs to have regular surveillance. The larger the size of the tumor the more is the chance of developing complications. We present a case with large chorioangioma without any serious complications and a successful outcome. DOI: http://dx.doi.org/10.3329/birdem.v2i2.12326 (Birdem Med J 2012; 2(2): 113-115)